2021
DOI: 10.3390/healthcare9060778
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prediction Models for Venous Thromboembolism in Ambulatory Patients with Lung Cancer

Abstract: Venous thromboembolism (VTE) is a significant cause of mortality in patients with lung cancer. Despite the availability of a wide range of anticoagulants to help prevent thrombosis, thromboprophylaxis in ambulatory patients is a challenge due to its associated risk of haemorrhage. As a result, anticoagulation is only recommended in patients with a relatively high risk of VTE. Efforts have been made to develop predictive models for VTE risk assessment in cancer patients, but the availability of a reliable predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The prediction models used for VTE risk assessment of cancer patients include the Khorana score, PROTECHT score, COMPASS-CAT score, and CONKO score. These models have been developed and validated in patients with ambulatory lung cancer[ 16 ]. Khorana score is currently the most validated chemotherapy-related VTE risk assessment model, which is a reliable model based on five clinical and laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction models used for VTE risk assessment of cancer patients include the Khorana score, PROTECHT score, COMPASS-CAT score, and CONKO score. These models have been developed and validated in patients with ambulatory lung cancer[ 16 ]. Khorana score is currently the most validated chemotherapy-related VTE risk assessment model, which is a reliable model based on five clinical and laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…15 The COMPASS-CAT Score had an improved sensitivity of 83% but a worsened specificity of 51% (95% CIs were not reported). 22 In our recent brief review, we identified some risk prediction models for VTE in ambulatory patients with lung cancer; 23 however, their performance is still largely unclear. 10 11 15 22 24 It is still uncertain how many VTE prediction models in total are available and which prediction model best suits the clinical purpose in terms of a reliable predictive performance in ambulatory patients with lung cancer.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Previous studies have confirmed that VTE is a risk factor for many cancers, such as lung cancer [ 4 ], pancreatic cancer, and gastroesophageal cancer [ 5 ]. VTE is the most common complication in cancer patients and the second leading cause of death in cancer patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%